The role of SAGA in the transcription and export of mRNA - E. N. Nabirochkina; M. M. Kurshakova; S. G. Georgieva; D. V. Kopytova (Вавиловский журнал генетики и селекции)
SAGA/TFTC, which is a histone acetyltransferase complex, plays an important role in the regulation of transcription. We have identified that the metazoan TFTC/STAGA complexes had histone H2A and H2B deubiquitinase activity that is carried out by a DUBm (deubiquitination module). We studied the DUBm of SAGA in Drosophila melanogaster and identified Drosophila homologs of yeast DUBm components. Two subunits of DUBm (Sus1/ENY2 and Sgf11) were shown to have functions separate from DUBm function. Thus, Sus1/ENY2 was shown to be present in several different complexes. Sgf11 was found to be associated with the cap-binding complex (CBC) and recruited onto growing messenger ribonucleic acid (mRNA). Also, we have shown that Sgf11 interacted with the TREX-2/AMEX mRNA export complex and was essential for mRNA export from the nucleus. Immunostaining of the polytene chromosomes of Drosophila larvae revealed that Sgf11 is present at the sites of localization of snRNA genes. It was also found in immunostaining experiments that dPbp45, the subunit of the PBP complex, the key player in the snRNA transcription process, is associated not only with the snRNA gene localization sites, but with other sites of active transcription by PolII. We also revealed that Sgf11 was present at many active transcription sites in interbands and puffs on polytene chromosomes, Sgf11 was localized at all Brf1 (the component of the RNA polymerase III basal transcription complex) sites. We concluded that SAGA coactivated transcription of both the PolII and PolIII-dependent snRNA genes.